Uji Aktivitas Antibakteri Ekstrak Etanol Daun Waru Gunung (Hibiscus macrophyllus) dan Fraksinya terhadap Staphylococcus aureus - Afif Rifqie Maulana; Bawon Triatmoko; Mochammad Amrun Hidayat (Pustaka Kesehatan, 2021)
Infection is one of the main causes of world health problems, especially in developing countries like Indonesia, one of which is an acute respiratory infection caused by bacteria such as Staphylococcus aureus. Therapeutics are used for the treatment of infections today with antibiotics. However, there are many cases of bacterial resistance to antibiotics that need to develop alternatives derived from plants. One of the plants that have antibacterial activity is the leaves of Waru Gunung (Hibiscus macrophyllus). The purpose of this study was to determine whether the ethanolic extract of H. macrophyllus leaves and their fractions have antibacterial activity against S. aureus. The method used in this antibacterial activity test is the disk diffusion method with a test concentration of 5%, 10%, 15%, 20%, and 25%. The results of this study indicate that all test samples have antibacterial activity except in the water fraction. The highest antibacterial activity was obtained in the ethyl acetate fraction which attracted semipolar compounds in the ethanolic extract of H. macrophyllus leaves. The antibacterial activity of the test samples in sequence from high to low includes ethyl acetate fraction, ethanolic extract, n-hexane fraction, and water fraction.